Tamanhos de manivas de mandioca de mesa cultivar ‘venâncio’, irrigada e tratadas com acadian® - Prata, Romulo Costa (Universidade Federal Rural do Semi-Árido, 2018)
In order to reduce the amount of stem spent to establish cassava planting ground, when irrigated without decreasing productivity, this trial was carried out at the Mata Fresca farm of Melão Mossoró, in December 2015 in the municipality of Mossoró-RN and the harvest eight months later, with the cultivar Venâncio. The cultivation was in clay-sandy soil, using a localized irrigation system. The culture was spaced 1.5 mx 0.80 m (8.333 plants per hectare) and different stem sizes (4, 6, 8, 10 and 12 cm) and treated at different doses of Acadian® rooting (0.2, 4, 6 and 8 mL L-1) for five minutes. The stem sizes were characterized in relation to diameter, volume, number health sprout, fresh mass and dry mass and water content (estimation). A randomized complete block design with four replications and plots containing 10 useful plants was used. The plant survival rate, plant height, stem diameter, shoot and root production, and root dimensions were evaluated at the time of harvest. In the development of plants, the size of maniva influenced the percentage of dead plants, number of shoots per plant and yield of commercial roots. The size of the shoot did not influence the number of dead plants, number of shoots per plant and yield of commercial roots. Stem sizes did not induce at plant height and stem diameter. The use of rooting did not influence any of the evaluated units.
Monografia
Keywords: Material de plantio; Comprimento de manivas; Mandioca irrigada; Enraizante; Material of planting; Length of stem; Irrigated manioc; Rooting; CIENCIAS AGRARIAS::AGRONOMIA